PENGARUH BIOSTIMULAN EKSTRAK DAUN CENGKODOK (Melastoma malabathricum L.) TERHADAP PERTUMBUHAN DAN STRUKTUR ANATOMI PLANLET ANGGREK HITAM (Coelogyne pandurata Lindl) PADA TAHAP AKLIMATISASI - Zakiah, Zulfa; Turnip, Masnur (BUANA SAINS, 2024)
Cultured plants will adapt to new environmental conditions at the acclimatization stage. Changes that occur can observed through changes in morphological and anatomical structures.  The increase in the number of cells and the size of plant organs illustrates the process of changing the anatomical structure of plants. It is necessary to optimize the concentration of biostimulant given and see its effect on plant growth and anatomical structure, to explain the mechanism of action of biostimulants. The research aimed to determine the concentration of biostimulant cengkodok leaf extract on black orchid plants. The study used a completely randomized design consisting of 8 treatment levels of cengkodok leaf extract biostimulant concentration (0, 10, 20, 30, 40, 50, 60 and 70 mg/L).  The results showed that the concentration of cengkodok leaf extract 20 mg/L was the best concentration for the parameters of the number of leaves and the number of roots of black orchid planlets, respectively 2.5 leaves and 7.5 roots. The application of cengkodok leaf extract affects the anatomical structure characteristics of black orchids, including an increase in the thickness of leaf mesophyll tissue, stem cortex tissue, and roots.